Grandparents matter: Optimizing grandparents' involvement after child safety concerns. Issue 4 (26th April 2018) - Gair, Susan; Zuchowski, Ines; Munns, Lyn; Thorpe, Ros; Henderson, Debbie
Abstract: Across Australia and internationally, growing numbers of grandparents are becoming primary carers for grandchildren, both within and outside of formal state care arrangements. Underlying factors include family breakdown, family circumstances where parents are unable to care for their children, or where there are child safety concerns. Some grandparents report a pattern of initially providing care for grandchildren but then experiencing reduced or lost contact that sometimes is not restored, in turn impacting ongoing relationships with grandchildren. A prevailing concern is the disproportional numbers of Aboriginal children in state care in all Australian states. Reported here are findings from a recent partnership research project focused on optimizing grandparent contact and ongoing relationships with grandchildren after child safety concerns. Qualitative in‐depth interviews and focus groups were conducted with 77 participants. Findings revealed grandparents yearned to maintain a significant role in grandchildren's lives after child safety issues emerged, however, they often felt powerless, unsupported, and sidelined from decision‐making in the best interests of their grandchildren. Participants made strong recommendations for more inclusive processes.